Cranial osteology of the mid-Cretaceous elasmosaurid Thalassomedon haningtoni from the Western Interior Seaway of North America. (July 2021) - Sachs, Sven; Lindgren, Johan; Madzia, Daniel; Kear, Benjamin P.
Abstract: Thalassomedon haningtoni is one of the most completely preserved elasmosaurid plesiosaurians described to date. Unlike most other elasmosaurid fossils, both the holotype and a second referred specimen — which were recovered from the middle Cenomanian Graneros Shale in the mid-western USA — are represented by intact skulls with articulated postcranial skeletons. Thalassomedon haningtoni thus constitutes an ideal 'model elasmosaurid taxon' that contributes significant character state data towards resolving contested relationships within the clade. Here, we present a detailed reassessment of the cranial osteology of T. haningtoni with the aim of evaluating its disputed species-level monophyly, together with its broader phylogenetic affinities. We identify several key diagnostic cranial traits including a sharply tapered premaxillary rostrum with a pronounced dorsomedian ridge that extends to the tip of the snout, a proportionately very small and rounded external bony nasal opening, and an anisodont functional dentition that incorporates a pair of enlarged 'fangs' in the second maxillary tooth position. Our phylogenetic analyses using first-hand scores unequivocally support classification of the Graneros Shale specimens as conspecific. Furthermore, consistent nesting with other North American elasmosaurid taxa suggests that T. haningtoni could evidence successive lineage divergences that took place within the Western Interior Seaway during the middle to latest Cretaceous. Highlights: Redescription of the cranium, mandible and dentition from Thalassomedon haningtoni. New character state data demonstrate unequivocal species-level monophyly. Phylogenies reveal elasmosaurid lineage divergences in the Western Interior Seaway.